Coping with COVID-19: Exploring coping strategies, distress, and post-traumatic growth during the COVID-19 pandemic in Australia - Kavanagh, Bianca E.; O’Donohue, Josephine S.; Ashton, Melanie M.; Lotfaliany, Mojtaba; McCallum, Maddy; Wrobel, Anna L.; Croce, Sarah; Berk, Michael; Saunders, Lucy; Lai, Jerry; Berk, Lesley (Frontiers in Psychiatry, 2022)
Objective: This study aimed to explore coping strategies, distress, and post-traumatic growth among Australians with and without a history of a mental health diagnosis during the COVID-19 pandemic. Methods: Australians (N=381) completed an online survey between 4-August 2020 and 25-October-2020. Coping strategies, distress, and post-traumatic growth were ascertained via the Brief COPE, Depression Anxiety and Stress Scale (DASS-21), and Post-Traumatic Growth Inventory (PTGI), respectively. Linear regression was conducted to examine the relationship between the Brief COPE, DASS-21, and PTGI, adjusting for sociodemographic factors. Models were conducted separately for those with/without a history of a mental health diagnosis. Results: Higher distress was found among those with a history of a mental health diagnosis. Significant differences in the types of coping strategies associated with distress and post-traumatic growth were identified between the groups, however, behavioural disengagement and self-blame consistently predicted depression, anxiety, and stress. For those with a history of a mental health diagnosis, positive reframing decreased anxiety. Self-distraction was associated with post-traumatic growth across both groups. Conclusions: There are important differences in the way people with and without a history of a mental health diagnosis cope with the COVID-19 pandemic.